Safety, Tolerability, and Proof-Of-Concept Study of OKV-119, a Novel Exenatide Long-Term Drug Delivery System, in Healthy Cats - Klotsman, Michael; Adin, Christopher A.; Anderson, Wayne H.; Gilor, Chen (Frontiers in Veterinary Science, 2021)
Background: Glucagon-like peptide-1 (GLP-1) is an incretin hormone that plays an important role in glucose homeostasis and food intake. In people, GLP-1 receptor agonists (GLP-1RAs) are commonly used for the treatment of type 2 diabetes mellitus (DM) and obesity; however, nonadherence to injectable medications is common. OKV-119 is an investigational drug delivery system intended for subdermal implantation and delivery of the GLP-1RA exenatide for up to 6 months. Hypothesis/Objectives: Develop protocols for the subcutaneous (SC) insertion and removal of OKV-119 and to evaluate its tolerability, in vivo drug-releasing characteristics, and weight-loss effects in cats. Animals: Two cadaveric and nineteen purpose-bred cats. Methods: In cadavers, OKV-119 insertion protocol and imaging were performed at three SC locations. The safety and tolerability of OKV-119 implants were assessed in a small (n=4 cats) 62-day study. Weekly plasma exenatide concentrations and body weight were measured in a 42-day proof-of-concept study designed to evaluate OKV-119 prototypes implanted in cats (n=15). Results: In anesthetized cats, the duration of insertion and removal procedures was 1 to 2 minutes. OKV-119 was easily identified on radiographs, and well tolerated without any apparent implant site reactions. Following implantation, exanatide plasma concentrations were observed for up to 35 days. Plasma exenatide concentrations were correlated to weight loss. Conclusion and clinical importance: Our findings suggest that OKV-119 could be easily inserted and removed during a routine clinic visit and can be used to safely and effectively deliver exenatide. Future studies of OKV-119, configured to release exenatide for a longer extended months-long duration, are warranted to determine whether the combination of metabolic improvements and beneficial weight-loss, coupled with minimal impact on pet-owner’s lifestyle, lead to improved outcomes for obese cats and feline DM patients.